(untitled) (Research, Society and Development, 2021)
The objective of this study is to analyze the economic feasibility of implementing a rainwater catchment system to serve non-potable uses in vertical residential buildings in the city of João Pessoa, state of Paraíba, Brazil, and assess the willingness of the city’s population to pay a higher price for a property that has this rainwater catchment system. The first hypothesis considers a variation in the number of floors, ranging from 5 to 30. The second hypothesis considers a variation in the reservoir volume. The volumes considered and tested were 15m³, 25m³, 45m³ and 65m³. Thus, 104 scenarios were created. To verify the population’s interest in rainwater harvesting systems and the willingness to pay extra for these systems, a survey was carried out via google forms, for about 70 people. Overall, 79.8% of the scenarios have B/C greater than 1. To the 15m³ reservoir, which presented a greater economic attractiveness, 92.31% of the alternative scenarios B/C greater than 1. The 65m³ reservoir has only 65.38% of the B/C values greater than 1. The best performance was achieved for the scenario of 21 floors and 15m³ reservoir, with the B/C of 1.96, NPV of R24,446.92 and payback period in 9.3 years. The application of the forms revealed that 96.6% of the population is interested in acquiring a property with the development system and that 57.1% are willing to pay up to 2% more than the property’s value.